Finance and Development, March 2010. (Finance and Development; Finance and Development ;, 2010)
Prize or Penalty: When Sports Help Economies Score" looks at why countries vie to host the world's most costly sporting events. And, in a series of articles on "After the Crisis," we discuss why some countries were hit harder than others; how were shocks transmitted round the world, and whether protectionist pressures might intensify in 2010. As usual, we take on a number of hot topics, including housing prices, bankers' bonuses, Ponzi schemes, and inflation targeting. In "Picture This" we see that the number of hungry is on the rise, topping 1 billion. Our regular "People in Economics" column profiles Daron Acemoglu, the Turkish-born intellectual who won the American Economic Association's award in 2005 for the most influential U.S. economist under the age of 40. "Back to Basics" explains inflation; and "Data Spotlight" looks at how dollarization is declining in Latin America. Also includes articles by Nick Stern on climate change and Simon Johnson on bonuses and the "doomsday cycle.